PENILAIAN KEMATANGAN GONAD MELALUI USIA SPERMARKE ANAK LAKI-LAKI DI PERKOTAAN MANOKWARI PAPUA - Elda Irma Jeanne Joice Kawulur; Andika Andika; Sita Ratnawati (FMIPA Universitas Papua, 2023)
The first time sperm production experienced by a man as an early sign of gonadal maturity (spermarche) is still considered taboo and violates ethics to be discussed in public. As a sign of sexual maturity, the age at spermarche varies among individu and population. This study aims to determine the age at spermarche of boys in urban area of ​​Manokwari West Papua Province. The method used in this research is cross sectional with interview technique. Data collection of age at spermarche is done using status quo method. The mean age at spermarche was analyzed using a generalized linear model (GLM) probit analysis. The average age at spermarche of boys in urban area of ​​Manokwari, West Papua Province was 12.83 years younger than the age at spermarche in rural areas of West Papua and western Indonesia. These characteristic reveals the response of plasticity in understanding the natural history of a population.